Resident‐Led Neighborhood Development to Support Health: Identifying Strategies Using CBPR. Issue 3 (23rd July 2020) - Foell, Andrew; Purnell, Jason Q.; Barth, Rachel; Witthaus, Michelle; Murphy‐Watson, Timetria; Martinez, Sal; Foley, Mike
Abstract : Evidence suggests that where people live, learn, work, and play affects a range of health outcomes for children and adults. Differential access to social, economic, and environmental supports puts some community members at greater risk, leading to disparities in health and well‐being. The 2014 release of the For the Sake of All report highlighted persistent health disparities for African Americans in St. Louis, Missouri, and their social and economic impacts on the St. Louis region. This study extends this work by developing partnerships with community organizations and neighborhood residents to address health disparities. Community‐based participatory research (CBPR) methods were utilized to engage partners in a 10‐month research process to address community concerns that impact health. Seven community residents, neighborhood researchers, engaged in workshops to learn about the research process and used techniques to gather information to implement action strategies. Neighborhood researchers selected 14 vacant lots to implement their action plan, which included visions for repurposing the land into a community park, produced a report for dissemination, and organized a community action forum to communicate their findings. This study highlights a promising approach to promote healthy communities and health equity by empowering neighborhood residents using participatory methodologies. Highlights: Describes the development of a community‐based research partnership to address health disparities. Presents details of participatory research and community mobilization process to support health. Reports findings related to the socioecological and system‐level factors that influence health. Identifies recommendations to support health that are informed by local knowledge and expertise. Reflects on the successes and challenges of sustaining community‐based partnerships for health.